ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN BANGLI - Sanjaya, Gede Putra; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 5, Mei 2018 (pp. 868-1111), 2018)
The performance of regional development can be seen from quality of services provided by local government to community. The quality of service provided depends on the size of budget owned by local government. The reality of ability to exploit regional potential in era of regional autonomy is different in all regions. This research was conducted in Bangli Regency. The purpose is to analyze the influence of GDRP, Total Population, and Number of Travelers to Original Local Government Revenue (OLGR), either partially or simultaneously. This study uses secondary data with quantitative method. The analysis technique used is multiple linear regression. Based on the result of research indicates that the variable of GRDP, Total Population, and Number of Tourist have significant influence simultaneously to OLGR. Then the GDRP variable has a positive and significant effect partially to OLGR, then the number of residents has positive and not significant effect partially to OLGR and the number of tourists negatively and not significantly partially to OLGR of Bangli regency for period of 1994-2016. Keywords: Original Local Government Revenue, Gross Domestic Regional Product, Total Population, and Number of Tourists.